The Role of Brand Storytelling, Accessibility, and Ticket Pricing in Driving Leisure Intentions and Recreational Decisions: A Study of Dunia Fantasi (Dufan), Jakarta - Favorita, Danti; Eddyono, Fauziah (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2025)
Urban recreational destinations face increasing competition, requiring theme park managers to understand key drivers of consumer behavior. This study investigates the influence of brand storytelling, accessibility, and ticket pricing on recreational interest and recreation decisions at Dunia Fantasi (Dufan) Jakarta, targeting corporate workers under 45. An online survey collected data from 250 respondents, analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that brand storytelling, accessibility, and ticket pricing significantly affect recreational interest, which in turn strongly influences recreation decisions and functions as a primary mediator. Direct effects of accessibility and ticket pricing on recreation decisions are not significant. The study underscores the need to integrate emotional, functional, and financial dimensions in theme park marketing, emphasizing authentic brand narratives, ease of access, and value-based pricing. These strategies enhance urban amusement park competitiveness by fostering visitor engagement and informed decision-making.